PENGARUH PELATIHAN, PENDIDIKAN FORMAL, DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEUANGAN DAN ASET PROVINSI SULAWESI UTARA - Manumpil, Viani Teresia; Dotulong, Lucky O. H; Pandowo, Merinda H. CH (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to examine and analyze: (1) the simultaneous influence of Training, Formal Education, and Quality of Work Life on Employee Performance at the Regional Financial and Asset Management Agency of North Sulawesi Province; and (2) the partial influence of Training, Formal Education, and Quality of Work Life on Employee Performance at the same agency. This research uses a quantitative method, and data collection was carried out by distributing questionnaires to employees of the Regional Financial and Asset Management Agency. The sampling technique used was saturated sampling, with a total sample of 80 respondents.